Application of VITA technique for detection of the organized structures present in a turbulent boundary layer under an adverse pressure gradient - Dróżdż, A.; Elsner, W.; Drobniak, S. (Archives of Mechanics, 2011)
The paper concerns experimental investigations of turbulent boundary layer (TBL), developing on a flat plate at Reθ = 3000 under an adverse pressure gradient (APG) corresponding to the case of pressure variation at axial compressor blading. In particular, the paper deals with the analysis of bursting phenomena and coherent structures activity in TBL with the use of VITA technique. The interpretation of coherent structures was based on the analysis of conditionally averaged traces of u and v velocity components recorded by X-wire probe in several boundary layer regions. The paper describes the modification introduced into the VITA method, which enables to distinguish four types of coherent structures. This modification relies on the detection of instantaneous positive or negative gradients of u and v velocity traces. It was found that bursting process under the influence of adverse pressure gradient is damped near the wall and this phenomenon is even more pronounced in the outer region of turbulent boundary layer. Furthermore, the paper gives the consistent proof, that vortices developing in TBL create the effect of bursting present in velocity signal.